125 Results of a randomized phase ii trial of paclitaxel and carboplatin versus bleomycin, etoposide and cisplatin for newly diagnosed and recurrent chemonaive stromal ovarian tumors. (13th November 2020) - Brown, J; Miller, A; Moxley, K; Backes, F; Nagel, C; Bender, D; Miller, D; Powell, M; Westin, S; Bonebrake, A; Muller, C; Alvarez Secord, A; et al.
Abstract : Objectives: To determine the progression free survival (PFS) of paclitaxel and carboplatin (PC) versus bleomycin, etoposide, and cisplatin (BEP) for treatment of newly diagnosed Stage IIA-IV or recurrent chemotherapy-naive ovarian sex cord-stromal tumors (SCST). Methods: This study was a phase II, open-label, noninferiority trial. Eligible women with SCST were equally randomized to PC (6 cycles P 175 mg/m2 and C AUC=6 IV every 3 weeks), or BEP (4 cycles B 20 units/m2 IV push day 1, E 75 mg/m2 IV days 1–5, and cisplatin 20 mg/m2 IV days 1–5 every 3 weeks). The targeted 128 patient accrual and PFS hazard ratio (HR)=0.67 provided 85% power to exclude noninferiority margin HR=1.10. Results: 63 patients were accrued at the interim futility analysis (31 PC and 32 BEP). Median age was 48 years. 87% had granulosa cell tumors. 37% had measurable disease. The DSMB closed the study early for futility of PC. The futility analysis was supported by 21/16 PFS events on the PC/BEP arms respectively, with an estimated HR=1.12 [95% CI: 0.58 to 2.16]. Median PFS was 27.7 months [7.4 to 41.0] for PC and 19.7 months for BEP [95% CI: 10.4–52.7]. PC patients had fewer grade 3 or higher adverse events (PC 77% vs BEP 90%). Differences included infections (0 vs 10%), low neutrophil count (65% vs 84%), and low WBC (22 vs 40%). One death NOS occurred on PC. Conclusions: Compared to BEP, PC failed to improve PFS in ovarian SCSTs. PC showed a more favorable side effect profile.